Religion, Ritual and Ritualistic Objects - Nugteren, Albertina (Tineke) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This is a volume about the life and power of ritual objects in their religious ritual settings. In this Special Issue, we see a wide range of contributions on material culture and ritual practices across religions. By focusing on the dynamic interrelations between objects, ritual, and belief, it explores how religion happens through symbolic materiality. The ritual objects presented in this volume include: masks worn in the Dogon dance; antique ecclesiastical silver objects carried around in festive processions and shown in shrines in the southern Andes; funerary photographs and films functioning as mnemonic objects for grieving children; a dented rock surface perceived to be the god's footprint in the archaic place of pilgrimage, Gaya (India); a recovered manual of rituals (from Xiapu county) for Mani, the founder of Manichaeism, juxtaposed to a Manichaean painting from southern China; sacred stories and related sacred stones in the Alor-Pantar archipelago, Indonesia; lotus symbolism, indicating immortalizing plants in the mythic traditions of Egypt, the Levant, and Mesopotamia;